The Influence of Organizational Culture, Work Environment and Work Discipline on Job Satisfaction of Teachers at Boarding School - Suriadi Suriadi; M. Rafid; Zulkifli Zulkifli; Abdurohim Abdurohim; Damirah Damirah (Departement of Mathematics Education, 2023)
The purpose of this study is to determine how organizational tradition, work environment, and work behavior effect trainer activity delight. This study employs quantitative methodologies and makes use of strategies for gathering facts from the distribution of questionnaires and library records. 74 teachers made up the study's sample. The analytical method used has been multiple linear regression. Using the data analysis tool SPSS 20.0. With a sig F value of 0.000 < alpha 0.05 and an f-count value of 10.821 > f-table of 2.160, the findings of this study show that organizational culture, work discipline, and work environment all have an impact on teacher job satisfaction. With a sig t value of 0.003 < alpha 0.05 and a t-count value of 3.031 > 1.993 in t-table, the results of the t test demonstrate a significant link between the work environment and teacher job satisfaction. Organizational culture strongly influences teacher job satisfaction, with a sig t value of 0.040 < alpha 0.05 and a t-count value of 2.092 > t-table 1.993. Work discipline has a considerable impact on teachers' job satisfaction, with a t-count of 2.234 > t-table of 1.993 and a sig t value of 0.029 < alpha of 0.05.